2008
DOI: 10.1111/j.1440-1738.2008.00636.x
|View full text |Cite
|
Sign up to set email alerts
|

Metamorphic and cooling history of the Shimanto accretionary complex, Kyushu, Southwest Japan: Implications for the timing of out‐of‐sequence thrusting

Abstract: Illite crystallinity, K–Ar dating of illite, and fission‐track dating of zircon are analyzed in the hanging wall (Sampodake unit) and footwall (Mikado unit) of a seismogenic out‐of‐sequence thrust (Nobeoka thrust) within the Shimanto accretionary complex of central Kyushu, southwest Japan. The obtained metamorphic temperatures, and timing of metamorphism and cooling, reveal the tectono‐metamorphic evolution of the complex, and related development of the Nobeoka thrust. Illite crystallinity data indicate that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 50 publications
2
48
0
Order By: Relevance
“…Vitrinite reflectance analysis indicates that the maximum temperatures of the hanging wall and footwall were about 320 and 250 °C, respectively (Kondo et al, ). Similar temperatures have been estimated from chlorite–quartz–H 2 O geothermometry (Raimbourg, Tadahiro, Yamaguchi, Yamaguchi, & Kimura, ), illite crystallinity, and fission track analysis (Hara & Kimura, ). The temperature difference across the thrust suggests a total displacement of 8–14 km (Kondo et al, ).…”
Section: Geologic Settingsupporting
confidence: 74%
See 1 more Smart Citation
“…Vitrinite reflectance analysis indicates that the maximum temperatures of the hanging wall and footwall were about 320 and 250 °C, respectively (Kondo et al, ). Similar temperatures have been estimated from chlorite–quartz–H 2 O geothermometry (Raimbourg, Tadahiro, Yamaguchi, Yamaguchi, & Kimura, ), illite crystallinity, and fission track analysis (Hara & Kimura, ). The temperature difference across the thrust suggests a total displacement of 8–14 km (Kondo et al, ).…”
Section: Geologic Settingsupporting
confidence: 74%
“…The intersection of the sub‐horizontal thrust trace with the mountainous topography leads to the exposure of klippe about 60 km south of the main thrust (Murata, ). The faulting is estimated to have occurred around 40–48 Ma, based on illite K–Ar and zircon fission track dating (Hara & Kimura, ). Pseudotachylyte is observed near the fault core in the hanging wall, confirming that the fault experienced seismic slip events (Okamoto et al, 2006).…”
Section: Geologic Settingmentioning
confidence: 99%
“…Radiolarian fossils yield ages that aid the reconstruction of the accretionary complexes, and reveal that the Shimanto accretionary complex grew oceanwards from the Late Cretaceous to the Early Miocene (e.g., Taira et al, 1988). Previous studies have used KeAr dating of illite, and fission-track dating of detrital zircon and apatite, to estimate the timing of metamorphism and cooling in the low-grade accretionary complex surrounding the study area (Agar et al, 1989;Hasebe et al, 1993;Tagami et al, 1995;Ohmori et al, 1997;Hasebe and Tagami, 2001;Hara and Kimura, 2008). Agar et al (1989) reported that the KeAr age of the m elange cleavage of the western Shikoku coastal area is 0e10 Myr younger than the depositional age, and that the complex cooled below about 100 C (the apatite closure temperature) at ca.…”
Section: Geological Setting Of the Shimanto Accretionary Complexmentioning
confidence: 99%
“…The Nobeoka Thrust in Kyushu also most likely represents a seismogenic out‐of‐sequence thrust (Fukuchi et al, ; Hamahashi et al, ; Kimura et al, ; Kondo et al, ; Mukoyoshi et al, ) that corresponds to the Aki Tectonic Line. Hara and Kimura () report an illite K–Ar age of 49 Ma (barring older ages influenced by detrital mica) for a phyllitic shale and zircon FT ages of 48 Ma and 46 Ma for sandstones within the Sampodake unit, which forms the hanging wall of the Nobeoka Thrust. They concluded that the Sampodake unit began post‐metamorphic cooling after 48 Ma, and was thrust over the Mikado unit about 40 Ma (the older limit of the depositional age of this unit) along the Nobeoka Thrust, suggesting that this thrust was active after 48–40 Ma.…”
Section: Discussionmentioning
confidence: 99%